Energy Intake and Energy Expenditure for Determining Excess Weight Gain in Pregnant Women. Issue 5 (May 2016) - Gilmore, L. Anne; Butte, Nancy F.; Ravussin, Eric; Han, Hongmei; Burton, Jeffrey H.; Redman, Leanne M.
Abstract : OBJECTIVE: To conduct a secondary analysis designed to test whether gestational weight gain is the result of increased energy intake or adaptive changes in energy expenditures. METHODS: In this secondary analysis, energy intake and energy expenditure of 45 pregnant women (body mass index [BMI] 18.5–24.9 [n=33] and BMI 25 or greater [n=12]) were measured preconceptionally and at 22 and 36 weeks of gestation. Energy intake was calculated as the sum of total energy expenditure measured by doubly-labeled water and energy deposition determined by the four-compartment body composition model. Measurements of weight, body composition, and basal metabolic rate were completed preconceptionally and 9, 22, and 36 weeks of gestation. Basal metabolic rate was measured by indirect calorimetry in a room calorimeter and activity energy expenditure by doubly-labeled water. RESULTS: Energy intake from 22 to 36 weeks of gestation was significantly higher in high gainers (n=19) (3, 437±99 kcal per day) compared with low+ideal gainers (n=26) (2, 687±110, P <.001) within both BMI categories. Basal metabolic rate increased in proportion to gestational weight gain; however, basal metabolic rate adjusted for body composition changes with gestational weight gain was not significantly different between high gainers and low+ideal gainers (151±33 compared with 129±36 kcal per day; P =.66). Activity energy expenditure decreased throughout pregnancy in both groups (low+ideal gainers: −150±70 kcal per day; P =.04 and high gainers: −230±92 kcal per day; P =.01), but there was no difference between high gainers and low+ideal gainers ( P =.49). CONCLUSION: Interventions designed to increase adherence to the Institute of Medicine guidelines for weight gain in pregnancy may have increased efficacy if focused on limiting energy intake while increasing nutrient density and maintaining levels of physical activity. Abstract : Gestational weight gain above the Institute of Medicine guidelines is achieved by an increased energy intake and not a thrifty metabolism.